Hannah Arendt [videorecording (DVD)] - Trotta, Margarethe von; Sukowa, Barbara, 1950-; Milberg, Axel; McTeer, Janet; Jentsch, Julia, 1978-; Noethen, Ulrich, 1959-; Degen, Michael, 1932-; Woodeson, Nicholas ([publisher not identified], 2013)
A brilliant biopic of the influential German-Jewish philosopher and political theorist. Arendt's reporting on the 1961 trial of ex-Nazi Adolf Eichmann in The New Yorker, controversial both for her portrayal of Eichmann and the Jewish councils, introduced her now-famous concept of the 'Banality of Evil.' Using footage from the actual Eichmann trial and weaving a narrative that spans three countries, von Trotta beautifully turns the often invisible passion for thought into dramatic cinema.